(untitled) (Analysis in Theory and Applications, 2022)
We show that the classical Brezis-Nirenberg problem -Δ u=u|u|+λ u in Ω, u=0 on Ω, when Ω is a bounded domain in R^6 has a sign-changing solution which blows-up at a point in Ω as λ approaches a suitable value λ_0>0.